FEASIBILITY ANALYSIS OF CHILD-FRIENDLY DISASTER RESPONSE EDUCATIONAL COMICS AS A SOCIAL STUDY LEARNING MEDIUM IN ELEMENTARY SCHOOLS - Ika Ari Pratiwi; Eko Handoyo; Ani Rusilowati; Trimurtini Trimurtini (Program Studi PGSD Universitas Flores, 2026)
Flood disasters remain a major challenge in elementary schools in the Kudus area, while disaster mitigation learning in social studies has not been optimally implemented. This condition leads to limited student understanding of risks and disaster response measures. This study aims to analyze the feasibility of the child-friendly educational comic